Antimicrobial Prescriptions for Dogs in the Capital of Spain - Gómez-Poveda, Bárbara; Moreno, Miguel A. (Frontiers in Veterinary Science, 2018)
Objective: to characterize antimicrobial usage patterns in urban dogs in veterinary practices in Spain using the city of Madrid as a model. Design: retrospective survey. Settings: dogs attending veterinary practices of the city of Madrid in 2017 were enrolled. Participants: 300 dogs from 30 veterinary practices randomly selected from a frame of 388 practices grouped per zip code. The Inclusion criterion for dogs was having been treated with antibiotics as nearest as possible to the day of data collection. Results: From the 300 dogs enrolled, 374 treatments with antimicrobials were recorded, 62.8% (235/374) being veterinary medicinal products and 37.2% (139/374) human medicinal products. The main route of administration was oral (209/374; 55.9%) followed by parenteral (100/374; 26.7%) and topical (65/374; 17.4%). Sixty-five of 300 dogs (21.7%) received a perioperative antimicrobial treatment, mainly associated with obstetrical female surgery (19/65; 29%), while 78.3% (235/300) received a medical treatment mainly for skin (72/235; 30.6%), respiratory (47/235; 20%) and digestive (41/235; 17.4%) diseases. The most frequently used antimicrobials were beta lactams for oral (119/209) and parenteral (79/100) use, especially the combination amoxicillin with clavulanic acid (83/209; oral use) and amoxicillin (42/100; parenteral use), and aminoglycosides (32/65) for topical use. Only in 13 of the 300 dogs, diagnostic confirmation with culture was carried out and nine underwent an antimicrobial susceptibility test. In addition, cytology was performed in 15 dogs. Conclusions: the pattern of antimicrobial usage in urban dogs in Spain is quite similar to that described in other European countries, and encompass the same two highly interconnected key features: major use of amoxicillin with clavulanic acid and very low level of antimicrobial susceptibility testing guiding prescription. Consequently, the measures for improving antimicrobial usage in dogs in Spain should follow those implemented in other countries.